An investigation into the relationship between the impact of HIV/AIDS on children and the changing role of educators in Dalindyebo Hich School in the Mthatha District, Eastern Cape - Ntshangase, Gloria Ntombovuyo (Stellenbosch : Stellenbosch University, 2012)
Assignment (MPhil)--University of Stellenbosch, 2007.